TINJAUAN FASILITAS DI OBJEK WISATA CANDI MUARA TAKUS KECAMATAN XII KOTO KAMPAR PROVINSI RIAU - Galih Ichsan Nuur Muhammad; Syofia Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study aims todescribe theexisting facilities Attractions: Candi Muara Takus XIII Sub-district Koto Kampar, andhow theres ponsesof visitorsabout the facilities available, in the form ofmajor facilities, support facilities and support facilities.This study uses quantitative methods with descriptive eapproachto solvethe problemsin the lift. The sample in this study as many as100 people were taken by usinga ccidental sampling. While collection techniques in this study using observation, questioner, interview and documentation. Byusing a Likert scaleas a measure todeter mine thelength of the short interval.Based on the research that has been done, the public response to the facilities availableat the Temple Barelang still lacking.The buildings are not sotreated and clean lines is alsovery less. And have many buildings that are ready tobe built, but to datenot usedat all.Keywords: Overview of facilities, Candi Muara Takus, XIII Sub-district Koto Kampar